2017
DOI: 10.1159/000474942
|View full text |Cite
|
Sign up to set email alerts
|

Pial Arteriovenous Fistula and Capillary Malformation-Arteriovenous Malformation Associated with <b><i>RASA1</i></b> Mutation: 2 Pediatric Cases with Successful Surgical Management

Abstract: We present case reports of 2 pediatric patients who were both found to have pial arteriovenous fistulas (AVFs) with subsequent genetic analysis revealing mutations in the RASA1 gene. Considering their family history of distinct cutaneous lesions, these mutations were likely inherited as opposed to de novo mutations. Patient 1 had large capillary malformations on the left side of the face and neck, associated with macrocephaly, and presented at the age of 32 months with speech delay, right-sided weakness, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…This is supported by the high prevalence of AVS-associated hereditary syndromes seen among children in this analysis. A proportion of pediatric SAVS cases may be caused by defects in key angiogenic signaling pathways (eg, TGFβ-BMP22 23; RAS-BRAF-MEK-ERK24 25; PIK3CA-AKT-mTOR26). These may occur through heterozygous germline mutations known to cause familial syndromes or sporadic mutations that occur throughout the lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by the high prevalence of AVS-associated hereditary syndromes seen among children in this analysis. A proportion of pediatric SAVS cases may be caused by defects in key angiogenic signaling pathways (eg, TGFβ-BMP22 23; RAS-BRAF-MEK-ERK24 25; PIK3CA-AKT-mTOR26). These may occur through heterozygous germline mutations known to cause familial syndromes or sporadic mutations that occur throughout the lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…3,5 In support of this, CMs in patients with CM-AVM syndrome tend to grow and increase in number in childhood, and AV shunts have been identified within the CMs. 1,4,6 Thus, it may be possible that patients with CM-AVM syndrome are highly likely to naturally develop a de novo AVM after birth even without neurovascular intervention.…”
Section: Discussionmentioning
confidence: 99%
“…1 Concurrent development of arteriovenous fistulas (AVFs) and AVMs has been observed in the skin, muscles, bones, internal organs, and the brain. 14 Recently, two phenotypes of CM-AVM syndrome have been identified: type 1 (CM-AVM1), caused by RASA1 mutations, and type 2 (CM-AVM2), caused by EPHB4 mutations. 5 The frequency of development of high-flow vascular lesions among patients with CM-AVM syndrome is reported to be approximately 26–32.6%.…”
Section: Introductionmentioning
confidence: 99%
“…This constellation of VMs related to RASA1 mutations was named capillary malformation -arteriovenous malformation syndrome (CM-AVM) [1]. Subsequently, a number of studies reported on atypical CMs caused by RASA1 mutations [2,3,5,6,[11][12][13][14][15][16][17][18][19][20][21][22][23]. It was demonstrated that alterations of RASA1 might also act as an additional factor in other vascular development disorders, including vein of Galen malformations (VOGMs) and HHT [24][25][26].…”
Section: Capillary Malformation-arteriovenous Malformation Syndromementioning
confidence: 99%